2009
DOI: 10.1007/s11255-009-9585-2
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia associated with large-bone fracture in elderly patients

Abstract: Hyponatremia has been shown to be associated with gait disturbances, decreased mentation, and falls. The study objective was to determine the incidence of hyponatremia in patients who experienced a substantial skeletal fracture (hip/pelvis/femur). During an 18-month period from March 2007 to August 2008 serum sodium levels were evaluated in 364 cases of bone fracture in patients aged 65 years or older and in 364 nonfracture patients aged 65 years and older seen in an urban emergency room setting. The incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
96
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(107 citation statements)
references
References 19 publications
(23 reference statements)
7
96
0
4
Order By: Relevance
“…AVP could indeed be a primary determinant for the osteoporosis that is known to accompany chronic hyponatremic states (22)(23)(24)(25)(26)(27)(28), although high aldosterone levels, for example in SIADH, may contribute also (21). The latter is possible because hyperaldosteronism also has been shown to cause bone loss in rodents (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…AVP could indeed be a primary determinant for the osteoporosis that is known to accompany chronic hyponatremic states (22)(23)(24)(25)(26)(27)(28), although high aldosterone levels, for example in SIADH, may contribute also (21). The latter is possible because hyperaldosteronism also has been shown to cause bone loss in rodents (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…49 Hyponatremia, a common and potentially serious adverse event complicating the use of SSRIs in older adults, has been implicated in fractures in a small case-control study. 50 Antidepressants may also directly impair postural control. Increased postural sway was noted in depressed patients in the first week of treatment with sertraline, when compared with nortriptyline and controls.…”
Section: Antidepressants and Fallsmentioning
confidence: 99%
“…In a longitudinal analysis of data from the Osteoporotic Fractures in Men Study (MrOS), it was reported that after adjusting for age, BMI, study center, and other covariates, hyponatremia was associated with up to a doubling in the risk of hip and morphometric spine fractures, independent of BMD (25). Accordingly, aside from reduction in BMD, chronic hyponatremia has also been associated with increased fracture rates in elderly (4,8,11,(14)(15)(16) and with metabolic bone loss through an uncoupling of bone resorption and formation in rats indicating the effect of hyponatremia on bone quality (10). Cellular and molecular data have confirmed increased osteoclastic bone resorption in response to low extracellular sodium levels (26) which represents attempts of the body to preserve sodium homeostasis at the expense of bone structural integrity leading hyponatremia-induced bone resorption and osteoporosis (13).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hyponatremia has been associated with increased fracture rate (4,(14)(15)(16) as well as osteoporosis at the femoral neck and total hip (13) in humans and with metabolic bone loss in rats (10).…”
Section: Introductionmentioning
confidence: 99%